Dynamic analysis of time fractional order oxygen in a plankton system - Sekerci, Yadigar; Ozarslan, Ramazan (Springer Heidelberg, 2020)
Oxygen production by marine phytoplankton has great importance to reveal the underlying structure of the aquamarine ecosystem. Any change in phytoplankton productivity may influence the marine biodiversity substantially as in fisheries and food supplies; hence, working on plankton is so crucial to detail the ocean biology. In this paper, we study a fractional model for the dynamics of oxygen, phytoplankton and zooplankton within Caputo sense to detail predation effect on oxygen-plankton system. We investigate into this time fractional model by the help of fractional numerical calculations and the parameters are chosen hypothetically in line with the results obtained from classical differential equations. We observe that species distribution and oxygen concentration show similar properties in fractional case while alpha =1 with the classical case; it foresees potential oxygen depletion under determined environmental conditions.
Keywords: Model; Algorithms